DETERMINAN PENGAMBILAN KEPUTUSAN INVESTASI BERDASARKAN NORMA SUBJEKTIF, KONTROL PERILAKU, DAN PERILAKU HEURISTIK - Rosadi Wirawan; Titik Mildawati; Bambang Suryono (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2022)
This study aims to obtain empirical evidence of the influence of Subjective Norms, Behavioral Control, and Heuristic Behavior on Investment Decisions. We used 54 respondents of individual investors who are just learning and or have already transacted on the Indonesia Stock Exchange (BEI) as a sample. By using multiple regression analysis, we found that the subjective norm has an effect on investment decisions. This means that the higher the influence of individual external environmental pressures, namely observers, friends, mass media, and investment management, the greater the individual's ability to make investment decisions. Behavioral Control has an effect on Investment Decisions. This means an understanding of the simplicity or complexity of taking action based on past experience and the obstacles that may be faced when taking action, affecting individuals in making investments. Heuristic behavior affects investment decision making. This means that the level of confidence and experience possessed by individuals and other known people will influence individuals in making accurate investments.